2002
DOI: 10.1159/000066538
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Acid Resistance of CO<sub>2</sub>and Nd-YAG Laser-Treated Human Tooth Enamel

Abstract: The purposes of this study were to test the effectiveness of laser treatment (pulsed CO2 and pulsed Nd-YAG) on in vitro acid resistance of human enamel. Thirty enamel surfaces were prepared from 10 extracted permanent premolars (3 surfaces per tooth). Two experimental surfaces on each tooth were irradiated with either CO2 or Nd-YAG lasers. All specimens were demineralized in 10 ml lactate buffer for 24 or 72 h after laser treatment. After 24-hour acid treatment the mean concentration of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
2
24

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 29 publications
2
33
2
24
Order By: Relevance
“…This cracked surface may be more susceptible to acid challenge. 24 Lan et al 26 showed that energy levels inducing crater formation by the Nd:YAG laser ranged from 100-150 mJ, which is much lower than the energy levels we used in the present study. Similarly to the results of the present study, Tsai et al 24 found no protective effect of Nd:YAG laser treatment on enamel demineralization in vitro.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This cracked surface may be more susceptible to acid challenge. 24 Lan et al 26 showed that energy levels inducing crater formation by the Nd:YAG laser ranged from 100-150 mJ, which is much lower than the energy levels we used in the present study. Similarly to the results of the present study, Tsai et al 24 found no protective effect of Nd:YAG laser treatment on enamel demineralization in vitro.…”
Section: Discussioncontrasting
confidence: 55%
“…24 Lan et al 26 showed that energy levels inducing crater formation by the Nd:YAG laser ranged from 100-150 mJ, which is much lower than the energy levels we used in the present study. Similarly to the results of the present study, Tsai et al 24 found no protective effect of Nd:YAG laser treatment on enamel demineralization in vitro. The pulsed Nd:YAG laser (83.33 J/cm 2 ) was unable to increase the enamel's resistance to acid challenge (lactate buffer solution, pH 4.5, for 24 and 72 h), as shown by calcium analysis and polarized light microscopy.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The caries-preventive effect produced on the enamel surface due to CO 2 laser irradiation was reported by Stern et al (Stern, et al, 1972). Subsequently, several studies, both in vitro Kantorowitz, et al, 1998;Hsu, et al, 2000;Tsai, et al, 2002) and in vivo (Kato, et al, 2003), have shown increases in enamel acid resistance.…”
Section: Co 2 Lasermentioning
confidence: 88%
“…Other researchers have reported that CO2-laser light application through a fluoride solution could be effective in the prevention of caries [18][19][20][21] . However, this treatment is insufficient where small defects are present in the enamel requiring some restorative treatment.…”
Section: Discussionmentioning
confidence: 99%